Mindfulness Based Childbirth Education: incorporating adult and experiential learning with mindfulness based stress reduction in childbirth education - Hauck, Yvonne; Fisher, C.; Byrne, J.; Bayes, S. (2016)
Informed choice is an expectation of today’s parents. Concern is evident around whether education models are evolving to ensure flexibility for parents to access options perceived as meeting their needs. Historical and current evidence around childbirth education models including the introduction of mindfulness to parent education will be presented. The aim of this article is to describe the rationale for incorporating adult and experiential learning with mindfulness-based stress reduction in a childbirth education program implemented in Western Australia. The curriculum of the Mindfulness Based Childbirth Education 8-week program is shared with corresponding learning objectives for each session. Examples of educational materials that demonstrate how adult and experiential learning were embedded in the curriculum are presented.